Modernidade e pós-modernidade: em busca do sentido da vida atual - Nogueira, Marco Aurélio [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2012)
This paper refl ects on a set of themes that are part of the contemporary agenda. The article contrasts modernity and post-modernity to discuss the “new sociology” which is dedicated to interpret the world and the way of life derived from the digital revolution and an intense capitalist globalization. Accepting some of the metaphors and concepts developed by this sociology, the paper argues that the world suggests much more than the image of a “radicalized modernity”, in which the dynamics of the past collide and combine with dynamics that are coming into existence, forming a plural, uneven, and surprisingly fast system.

O presente texto pretende refl etir sobre um conjunto de temas que integram a agenda contemporânea. Toma como ponto de partida a contraposição entre modernidade e pós-modernidade para dialogar a “nova sociologia” que se encontra em constituição, dedicada a interpretar o mundo e o modo de vida derivados da revolução digital e da globalização capitalista intensifi cada. Mediante a aceitação de algumas das metáforas e dos conceitos postos em circulação por essa sociologia, busca-se argumentar que o mundo que temos diante dos olhos sugere bem mais a imagem de uma modernidade radicalizada, na qual se chocam e se combinam dinâmicas do passado com dinâmicas que estão apenas se anunciando, formando um conjunto compósito, plural, desigual, surpreendente e veloz.
Modernity and post-modernity: in search of the meaning of the current life
Keywords: Modernity; Liquid life; Individualization; Risk society; Modernidade; Vida líquida; Individualização; Sociedade do risco